2016
DOI: 10.22159/ajpcr.2016.v9s3.14023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daidzein 120 Mg Supplementation to Menopausal Symptoms and Quality of Life in Non Equol Producer Women

Abstract: Objectives: To investigate and compare symptom changes and quality of life (QOL) in non equol producer postmenopausal women after consuming daidzein supplementation.Methods: This was a single randomized clinical trial. It involved menopausal women. They were divided into two groups, one received placebo that contains calcium glycerophosphate 500 mg, vitamin D3 35 IU and daidzein group contain daidzein 120 mg, contain calcium glycerophosphate 500 mg, vitamin D3 140 IU for 8 weeks. Plasma equol was measured befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These results are in line with studies in sheep that supplementation with Selenium 0.15 mg/kg increased serum Se levels linearly with increasing duration of experimental feeding for 30; 60; and 90 days. 21 Similar results were reported that 12 weeks of supplementation with 400 mg Q10 and 200 g selenium per day in women aged 58 years significantly increased serum Q10 and selenium levels compared with placebo [15]. In this research, there was no correlation between selenium levels and menopausal complaints based on MENQOL on all disorder aspects both before and after selenium administration.…”
Section: Discussionsupporting
confidence: 73%
“…These results are in line with studies in sheep that supplementation with Selenium 0.15 mg/kg increased serum Se levels linearly with increasing duration of experimental feeding for 30; 60; and 90 days. 21 Similar results were reported that 12 weeks of supplementation with 400 mg Q10 and 200 g selenium per day in women aged 58 years significantly increased serum Q10 and selenium levels compared with placebo [15]. In this research, there was no correlation between selenium levels and menopausal complaints based on MENQOL on all disorder aspects both before and after selenium administration.…”
Section: Discussionsupporting
confidence: 73%
“…There is a need to treat depression by taking antidepressants. Besides psychological factors, several behavioural and environmental factors also raise the problem of sexual dysfunction which includes conditions like obesity, overweight, physical inactivity, (Muharam et al, 2016) etc. Obese women are more likely to have more severe and a significant number of sexual problems (Lewis et al, 2010).…”
Section: Risk Factormentioning
confidence: 99%
“…Genistein and daidzein were able to suppress bone loss too [11]. In non-equol producer women, supplementation of daidzein did not significantly decrease the menopausal symptoms nor improve their quality of life [12]. Isoflavones are also able to improve cognitive function through the protective mechanism of the nervous system [13].…”
Section: Introductionmentioning
confidence: 99%